1999
DOI: 10.1023/a:1006173313548
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A mutant line of Pisum fulvum was identified that lacked seed lipoxygenase-2 (LOX-2). The mutant phenotype was introgressed into a standard Pisum sativum cv. Birte to provide near-isogenic lines with or without seed LOX-2. Genetic analyses showed the mutation to behave as a single, recessive Mendelian gene. Northern and dot-blot analyses showed a large reduction in LOX-2 mRNA from developing seeds of the LOX-2-null mutant. A restriction fragment length polymorphism associated with the 5' end of the LOX-2 gene(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“… 42 The studied genotypes show noticeable variation in the intensity of lipoxygenase bands ( Figure S2 ), but establishing the significance of this variation requires further scrutiny. In other legumes such as soybean 43 and pea, 44 efforts to develop genotypes lacking the major seed protein lipoxygenase have been successful.…”
Section: Results and Discussionmentioning
confidence: 99%
“… 42 The studied genotypes show noticeable variation in the intensity of lipoxygenase bands ( Figure S2 ), but establishing the significance of this variation requires further scrutiny. In other legumes such as soybean 43 and pea, 44 efforts to develop genotypes lacking the major seed protein lipoxygenase have been successful.…”
Section: Results and Discussionmentioning
confidence: 99%
“…As such, both mutants provide opportunities for the combination of mutations in order to reduce the content of anti-nutritional proteins in seeds. Null mutations have been reported for albumin 2 [ 41 ] and a lipoxygenase enzyme [ 42 ] previously in pea. More recently, several null mutations were identified following high-throughput screens of a population generated by fast neutron mutagenesis of pea [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lipoxygenase (LOX)-promoted oxidation of lipids contributes some of the VOCs in protein ingredients. Forster et al (1999) reported a lower concentration of hydroperoxides were formed in a pea seed free of the enzyme LOX-2. Thus, the contribution of LOX in the generation of VOCs starts with hydroperoxide formation.…”
Section: Volatile Organic Compoundsmentioning
confidence: 98%